Nosocomial Omicron Outbreak in a Medical Ward During the Coronavirus Disease 2019 Pandemic - Lu TL; Chuang Y; Huang C (Dove Medical Press, 2023)
Tsung-Lung Lu,1 Yiling Chuang,1 Chienhsiu Huang2 1Department of Nursing, Dalin Tzu Chi Hospital, Buddhist Tzu Chi Medical Foundation, Chiayi County, Taiwan; 2Department of Internal Medicine, Dalin Tzu Chi Hospital, Buddhist Tzu Chi Medical Foundation, Chiayi County, TaiwanCorrespondence: Chienhsiu Huang, Department of Internal Medicine, Dalin Tzu Chi Hospital, Buddhist Tzu Chi Medical Foundation, NO. 2, Min-Sheng Road, Dalin Town, Chiayi County, Taiwan, Email hgssport@yahoo.com.tw; dm550671@tzi.com.twBackground: The Omicron variant of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is 2 to 3 times more contagious than the Delta variant and poses a new challenge in containing transmission in community and health care settings. Transmission in hospitals can cause nosocomial outbreak infections and affect patients and health care workers. This study describes a coronavirus disease 2019 (COVID-19) outbreak in a medical ward. The purpose of the investigation was to determine the transmission source of the outbreak, as well as the measures implemented to prevent and control it.Methods: A cluster of SARS-CoV-2 infections that affected health care workers, inpatients, and caregivers was thoroughly researched in a medical ward. There were several strict outbreak measures implemented in our hospital, and these measures controlled the nosocomial COVID-19 outbreak in this study.Results: Seven cases of SARS-CoV-2 infection were diagnosed within 2 days in the medical ward. The infection control team declared a nosocomial outbreak of the COVID-19 Omicron variant. Several strict outbreak measures were implemented as follows: 1. The medical ward was closed and cleaning and disinfection were performed. 2. All patients and caregivers with negative test results were transferred to a spare COVID-19 isolation ward. 3. Relatives' visits were not allowed, and no new patient was admitted during the outbreak period. 4. Health care workers were retrained on wearing personal protective equipment and enhanced techniques and practices of hand hygiene, social distancing, and self-monitoring of fever and respiratory symptoms.Conclusion: This outbreak occurred in a non-COVID-19 ward during the COVID-19 Omicron variant phase of the pandemic. Our strict outbreak measures halted and contained the nosocomial COVID-19 outbreak in 10 days. Future studies are needed to establish a standard policy of COVID-19 outbreak measure implementation.Keywords: SARS-CoV-2, COVID-19, nosocomial outbreak, medical ward, Omicron variant